Surveying and modelling of historical buildings using point cloud data in Suleymaniye in Istanbul, Turkey - Benli, Gülhan; Kan, Tuna (Taylor and Francis Ltd., 2017)
Suleymaniye was one of the most densely populated areas of Istanbul in the Ottoman period. In order to protect the traditional cultural identity of Suleymaniye region and bring it in line with contemporary living conditions, a new project has been created by the Istanbul Metropolitan Municipality. Within the framework of the research on cloud computing on architecture, this paper will present both the results of terrestrial laser scanning which was used to obtain 3D point clouds through 3D survey measurements and scans of silhouettes of streets and roads, which were then transposed into survey images and designed as an example of city modelling. Additionally, the study will cite examples of how this technology has been used in Suleymaniye region.
Keywords: Heritage List; Historical Buildings; Istanbul; Laser Scanning; Modelling; Ottoman Period; Point Cloud Data; Surveying